Síntesis y caracterización de complejos níquel y cobalto (ii), Contenidos en ligandos derivados de 3,5-dimetilpirazol para la Sensibilización de Tio2 y su aplicación en fotocatálisis heterogénea utilizando luz visible (2017)
In the present research project the synthesis of complexes was developed nickel and cobalt (II) metals contained in ligands derived from 3,5- dimethylpyrazole and TiO2 films were modified based on scientific articles.